Detecção de Salmonella spp. e Leptospira spp. em Phrynops geoffroanus (cágado-de-barbicha) em ambiente urbano - Oliveira, Juliana Paula de [UNESP] (2013)
Salmonella spp. e Leptospira spp., zoonotic agents of public health relevance, have higher occurrence in tropical regions and present in the aquatic environment, a viable survival and transmission way. This study aimed to investigate the presence of Salmonella spp. and Leptospira spp. in Phrynops geoffroanus (geoffroy’s side-necked turtle) and the presence of Salmonella spp. in the environment (Cerradinho Stream, Jaboticabal-SP), where animals were captured. From blood samples and cloacal swabs of P. geoffroanus and samples of water and sediment from the stream, microbiological cultures for Salmonella spp. were performed. The serum of P. geoffroanus was used to detect antibodies anti-Leptospira spp. by microscopic agglutination test (MAT). Polymerase chain reaction (PCR) technique was used to verify the presence of Leptospira spp. in samples of gastric and cloacal lavage. Several serotypes of Salmonella spp. were isolated in samples of Cerradinho stream and cloacal swabs of P. geoffroanus residents in this environment. The serotypes of Salmonella spp. found in the environment and in P. geoffroanus were not always the same. The freshwater testudines were positive for Leptospira spp., and antibody against the agent were detected. It was concluded that the presence of agents, in both animals and aquatic environment, may represent a risk to public health